User interaction technique with 3D object manipulation in augmented reality environment - Ajune Wanis Ismail, 1985-; Mohd. Shahrizal Sunar, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (2011)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2011